Brain atrophy and disability progression in multiple sclerosis patients: a 10-year follow-up study - Jacobsen, Cecilie; Hagemeier, Jesper; Myhr, Kjell-Morten; Nyland, Harald; Lode, Kirsten; Bergsland, Niels; Ramasamy, Deepa P; Dalaker, Turi O; Larsen, Jan Petter; Farbu, Elisabeth; Zivadinov, Robert (Journal of neurology, neurosurgery and psychiatry, 2014)
To identify MRI biomarkers associated with long-term disability progression in patients with multiple sclerosis (MS), and to define the rate of evolution of global, tissue-specific and regional atrophy in patients with MS over long-term. MRI of the brain and clinical neurological assessment was performed in 81 patients at time of first visit and after 5 and 10 years of follow-up. MRI was acquired on 1.5 T scanners. T1-lesion and T2-lesion volumes (LVs) were calculated. Global and tissue-specific atrophy changes were longitudinally assessed, using a direct measurement approach, by calculating percentage volume changes between different time points. Regional tissue volumes for the subcortical deep grey matter (SDGM) structures were also obtained. Disability progression was defined as an increase in Expanded Disability Status Scale of ≥ 1.0 compared to baseline at 5-year and 10-year follow-up. Over 5 years, patients with disability progression showed significantly increased loss of whole brain (-3.8% vs -2.0%, p<0.001), cortical (-3.4% vs -1.8%, p=0.009) and putamen volume changes (-10.6% vs -3.8%, p=0.003) compared to patients with no disability progression. No significant change in white matter (WM) volume was observed when comparing progressing and non-progressing patients. Over 10 years, there was a trend for greater decrease in whole brain volume (-5.5% vs -3.7%, p=0.015) in the progressing patients. No significant changes in LV measures were detected between the patients with and without disability progression. This long-term study shows that whole brain, cortical and putamen atrophy occurs throughout the 10-year follow-up of this MS cohort and is more pronounced in the group that showed disability progression at 5, but not at 10 years of follow-up. Overall, GM atrophy showed better association with disease progression than WM atrophy over 5-year and 10-year follow-up.